Stochastic and deterministic models for agricultural production networks - P. Bai; H.T. Banks; S. Dediu; A.Y. Govan; M. Last; A.L. Lloyd; H.K. Nguyen; M.S. Olufsen; G. Rempala; B.D. Slenning (Mathematical Biosciences and Engineering)
An approach to modeling the impact of disturbances in anagricultural production network is presented. A stochastic modeland its approximate deterministic model for averages over samplepaths of the stochastic system are developed. Simulations,sensitivity and generalized sensitivity analyses are given.Finally, it is shown how diseases may be introduced into thenetwork and corresponding simulations are discussed.